2017
DOI: 10.5296/ber.v7i1.10524
|View full text |Cite
|
Sign up to set email alerts
|

Liquidity Risk and Bank Performance: An Empirical Test for Tunisian Banks

Abstract: An important part of banking literature was interested in the relationship between credit risk and bank performance. However, only few studies investigated the association between liquidity risk and bank performance. The aim of this paper is to study the effect of liquidity risk on the Tunisian bank performance. To this end, we used a sample of 10 Tunisian banks over the period 1990-2013. By applying panel data method, precisely random effect regression, results show that liquidity risk decreases significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
26
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 14 publications
(15 reference statements)
9
26
1
1
Order By: Relevance
“…Similar conclusions have been drawn by Bashir (2003), Staikouras and Wood (2004), and Sultan et al (2020). Conversely, Hakimi and Zaghdoudi (2017), based on a study of 10 Tunisian banks found a negative relationship between liquidity and bank performance. Godfrey (2015) and Farooq et al (2021) also reported similar findings in the respective studies as well.…”
Section: Liquidity Ratiosupporting
confidence: 80%
“…Similar conclusions have been drawn by Bashir (2003), Staikouras and Wood (2004), and Sultan et al (2020). Conversely, Hakimi and Zaghdoudi (2017), based on a study of 10 Tunisian banks found a negative relationship between liquidity and bank performance. Godfrey (2015) and Farooq et al (2021) also reported similar findings in the respective studies as well.…”
Section: Liquidity Ratiosupporting
confidence: 80%
“…LDR coefficient showed -0.1005 which indicates that a unit change in LDR will cause an inverse change in ROE. This outcome agrees with the findings of Bassey and Moses (2015) in Nigeria as well as Hakimi (2017) in Tunisia in similar studies where financial performance and liquidity risk measured by credit deposit ratio showed negative relationship. However, the result is at variance with that of Berrio (2013) in USA and Omid & Javaid (2016) in India where the same study gave a positive relationship between loan deposit ratio and ROE.…”
Section: Results Of the Panel Data Regression Analysissupporting
confidence: 92%
“…Table 1 presents the results of the credit risk, liquidity risk and insolvency risk impact on the return on equity of domestic and foreign Islamic banks in Malaysia. Concerning the fixed effect, the liquidity assets over total assets (LATA) and equity to assets (ETA) ratio showed negative and statistically significant impact on bank performance of both domestic Islamic banks in Malaysia over the study periods, which is consistent with several previous studies (Hakimi and Zaghdoudi;. This implies that one unit decreases in LATA and ETA is contributed to the one unit increase in liquidity risk in domestic Islamic banks.…”
Section: Return On Equity (Roe) Non-performing Loan (Npl) Loan Losssupporting
confidence: 88%